Currency exchange, its Illah and implications - Oziev, Gapur; Mohammed, Mustafa Omar; Zaidon, Muhammad Hafizi; Amafua, Mahfuth Khamis (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2016)
Foreign exchange is among the most important transaction in any economy. It can affect positively or negatively the relative price of domestic and foreign goods, which in turn has effect on the country’s economic growth, employment rate, inflation and balance of payment, among others. Yet, foreign exchange has remained a contentious issue among Muslim jurists and scholars. There are those who approve spot transactions but regard forward transactions as unlawful. Conversely, some scholars and jurists do not see any problem with the forward transactions if they are used for hedging purposes. This contention does bring into fore a pertinent research need of revisiting, in the context of modern business environment, the Illah (effective cause/reason) for determining whether a given foreign exchange transaction is Shari’ah compliant. The present study has critically reviewed the major literature and fatwas issued in relation to foreign exchange. It has adopted content analysis to categorize these various views on the subject and preponderated the major ones relevant to modern business. The authors have concluded that the only possible illah to be considered for the modern paper money is Athummuniyah (means of payment). The study concludes with recommendations and suggestions for future research.